Links between low-income population factors across Fergana and Namangan provinces - PhD. Z.A.Musaeva (Zien Journals, 2024)
The article comments on factors affecting poverty reduction in Fergana and Namangan Provinces: Economic Development, Employment and unemployment rate dependence, income inequality, and the reasons for the origin of poverty. The main emphasis is on the dependence of factors affecting poverty reduction, and explained that poverty reduction is influenced by subjective and objective processes.
Keywords: Economic growth; poverty